Effectiveness of thinner polyvinyl alcohol fibers on mechanical properties and cost effectiveness of office automation floor panels - Tek Raj Gyawali (PLoS ONE, 2025)
Floor finishing is the final and crucial stage in building construction. Flooring materials must possess strength, insulation, durability, aesthetics, and comfort. Office buildings typically use raised floor systems, known as office automation (OA) floors, which utilize various panel types for insulation and wiring purposes. Polyvinyl alcohol (PVA) fiber-reinforced mortar, with a water-cement (W/C) ratio of 0.30, a cement-sand (C:S) ratio of 1:0.776, and a fiber content of 3.0% by volume (fiber size: Ф100µm × 12mm), is mechanically pressed with water dehydration to create OA floor panels measuring 500 mm in length and width and 23 mm in thickness. A W/C ratio of 0.32 was maintained to achieve the same workability for producing panels using thinner PVA fibers (fiber size: Ф40µm × 12mm). A comparative analysis of both panel types was conducted, focusing on mechanical properties and costs. Panels reinforced with thinner PVA fibers exhibited superior performance in resisting compressive and impact loads. This enabled a reduction in fiber content to 1.2% (a 60% decrease) and panel thickness to 22 mm (a 4.35% decrease) compared to panels with thicker fibers. Consequently, the cost of panels with thinner fibers was reduced by 43.9%. The findings demonstrate that thinner PVA fibers are a viable replacement for thicker fibers in conventional OA floor panels, significantly reducing costs while meeting the required mechanical properties. The implementation of these findings in real OA floor factories reduces the consumption of PVA fibers and cement, contributing to sustainable development by lowering the carbon footprint, which is primarily generated during the production of cement and PVA fibers.